2021
DOI: 10.4067/s0718-58392021000200182
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in yield, nutritive value, and antioxidant capacity of leaves of alfalfa plants grown in arid climate of Saudi Arabia

Abstract: In addition to its high nutritional value, alfalfa (Medicago sativa L.) has several health benefits including antioxidant, neuroprotective, antimicrobial, antiulcer, hypocholesterolemic, hypolipidemic, and estrogenic effects. We aimed to assess the nutritional value and antioxidant capacity of alfalfa leaves at different times of the year in arid regions. Alfalfa was harvested in autumn, winter, spring, and summer and fresh yield and leaf:stem ratio were measured. Leaves were collected to determine their nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Within a certain range, it has been documented that the soluble sugar content in plant leaves increases proportionally with higher light intensities, as observed in various vegetables and crops such as spinach and soybeans (Almeida et al, 2021;Zou et al, 2020;). In this study, the soluble sugar content of alfalfa during a 30-day harvest period the shoot and root of alfalfa possess the ability to scavenge DPPH free radicals (Gao et al, 2020;Soufan et al, 2021). In this study, the DPPH free radical scavenging rate of ethanol extracts obtained from alfalfa during a 30-day harvest period exhibited a gradual increase under light treatments ranging from 400 to 600 µmol m −2 s −1 .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Within a certain range, it has been documented that the soluble sugar content in plant leaves increases proportionally with higher light intensities, as observed in various vegetables and crops such as spinach and soybeans (Almeida et al, 2021;Zou et al, 2020;). In this study, the soluble sugar content of alfalfa during a 30-day harvest period the shoot and root of alfalfa possess the ability to scavenge DPPH free radicals (Gao et al, 2020;Soufan et al, 2021). In this study, the DPPH free radical scavenging rate of ethanol extracts obtained from alfalfa during a 30-day harvest period exhibited a gradual increase under light treatments ranging from 400 to 600 µmol m −2 s −1 .…”
Section: Discussionmentioning
confidence: 74%
“…The evaluation of the antioxidant activity of plants often involves the utilization of the DPPH free radical scavenging rate. Previous studies have demonstrated that the ethanol extracts derived from both the shoot and root of alfalfa possess the ability to scavenge DPPH free radicals (Gao et al., 2020; Soufan et al., 2021). In this study, the DPPH free radical scavenging rate of ethanol extracts obtained from alfalfa during a 30‐day harvest period exhibited a gradual increase under light treatments ranging from 400 to 600 µmol m −2 s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results concurred with previous reports on other plants. The autumn (high total rainfall) harvest of Medicago sativa L. from Saudi Arabia provided high human nutrition (high crude protein and fat but low crude fiber) [25], while protein contents in Acacia brevispica, Acacia nilotica, Acacia seyal, Acacia tortilis, Balanites aegyptiaca, Grewia bicolor, Grewia tembensis, and Rhus natalensis from Southern Ethiopia harvested during the rainy season were higher than recorded in the hot dry season [26]. Similar results were observed in Cladium mariscus L. Pohl (sawgrass) from Southern Portugal, where crude protein and fat contents were higher in spring than during other seasons, while fiber was lowest [27].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the relationship between the biological activity of sorghum and the precipitation and climate of the growing region were conducted; however, it is difficult to determine their correlation because sorghum grows well even in a barren climate [9]. A study on the antioxidant activity and nutritional value of alfalfa leaves found that they were greatly influenced by climate according to seasonal changes [10]. The ascorbic acid content in potatoes varies considerably among cultivars exposed to different environments in Europe [11].…”
Section: Introductionmentioning
confidence: 99%